A method for metallizing graphene oxide holes in flexible copper-clad laminates
By using the use of oxide graphene aqueous solution and ultrasonic treatment on the flexible copper cover plate, the conductive layer is formed, which solves the problem of easy plating in the existing hole metal technology in the high -frequency circuit board, and realizes the uniform copper and conductive layer of the inner wall of the hole. Efficient formation.
Patent Information
- Application Number
- CN202210331517.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-31
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-03-31
AI Technical Summary
The existing pore metallization process is prone to leakage of conductive layers in high-frequency circuit board applications, which affects the chemical plating effect and leads to waste products.
Use the oxide graphene aqueous solution to soak the flexible copper covering plate, combined with ultrasound treatment and the use of pore agents, forming a strong electrostatic adsorption force and molecular bond force, so that the oxygen oxygenne is uniformly adsorbed on the wall of the hole, and it is stable through chemical copper plating to form stability The conductive layer.
The uniform copper of the inner wall of the hole is realized, the pore wall is smooth and smooth, without flaws, avoids leakage, and improves the conductivity of the conductive layer. It is suitable for the production of high -frequency circuit boards.
Smart Images

Figure CN114845480B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for metallizing graphene oxide holes in a flexible copper-clad plate, and belongs to the technical field of flexible circuit boards. Background Art
[0002] Flexible Printed Circuit (FPC) is a highly reliable and flexible printed circuit board made of polyimide or polyester film. It has the characteristics of high wiring density, light weight, thin thickness and good bendability. It is widely used in LCD and plasma flat panel displays in the fields of electronics and communications.
[0003] Flexible circuit boards are made on flexible copper-clad boards through certain processes. Flexible circuit boards can generally be divided into single-sided boards, double-sided boards and multi-layer boards. Double-sided boards and multi-layer boards have two layers of copper boards and multiple layers of copper boards, respectively, and the copper boards are separated by non-conductive substrates. Therefore, through holes are required between different copper layers to conduct the lines between layers. Since the substrate is a non-conductive material, copper cannot be plated on the substrate during chemical electroplating. Therefore, the hole wall of the through hole needs to be metallized (hole metallization) to make it conductive, so that chemical copper plating can proceed smoothly.
[0004] At present, there are three main processes for hole metallization: the first is to form a conductive layer from graphite or carbon black; the second is to use a layer of metal palladium as a seed layer; the third is to use pyrrole, thiophene, furan and aniline to polymerize on the hole wall to form a conductive polymer layer. However, the conductive layer formed by graphite or carbon black has poor conductivity, and due to the large particles, it is difficult to adhere when the through-hole size is small; metal palladium is difficult to mass produce due to its high cost; the polymer conductive layer is the most commonly used hole metallization process, but its polymerization process requires potassium permanganate solution for oxidation treatment, which has a certain degree of environmental pollution, and the formed polymer conductive layer has limited conductivity. When these traditional hole metallization processes are applied to some more complex high-frequency circuit boards, the hole wall of the circuit board often leaks the conductive layer, which seriously affects the subsequent chemical plating and causes waste. Therefore, there is still a lot of room for improvement in the hole metallization process. Summary of the invention
[0005] The present invention provides a method for metallizing graphene oxide holes in a flexible copper-clad laminate, which can effectively solve the above problems.
[0006] The present invention is achieved in that:
[0007] A method for metallizing graphene oxide holes in a flexible copper-clad laminate comprises immersing the flexible copper-clad laminate with through holes in a graphene oxide aqueous solution and then performing chemical copper plating.
[0008] As a further improvement, the concentration of the graphene oxide aqueous solution is 18-24wt%, and the treatment time is 2-10min.
[0009] As a further improvement, ultrasonic treatment is also performed during the immersion treatment.
[0010] As a further improvement, the frequency range of the ultrasonic wave in the ultrasonic treatment is 20-60 kHz.
[0011] As a further improvement, before the immersion treatment, a hole-leveling agent is used to perform hole-leveling treatment on the through holes of the flexible copper-clad laminate.
[0012] As a further improvement, after the immersion treatment, the through holes of the flexible copper clad laminate are also micro-etched with a micro-etching solution.
[0013] As a further improvement, the through hole is formed by drilling a hole on the surface of the flexible copper clad laminate using an ultraviolet laser drilling machine.
[0014] As a further improvement, the power of the ultraviolet laser drilling machine is 4.5W, the scanning speed is 50mm / s, and the number of repeated drilling times is 4 times.
[0015] As a further improvement, the graphene oxide is formed by a sufficient oxidation reaction of potassium permanganate and graphite powder in concentrated sulfuric acid.
[0016] A flexible copper clad laminate prepared by the above method.
[0017] The beneficial effects of the present invention are:
[0018] The present invention adopts graphene oxide solution to carry out hole metallization treatment, and graphene oxide microstructure is flaky, and when dispersed in solution, flaky graphene oxide is very easy to be adsorbed on the copper hole wall surface, and now has strong electrostatic adsorption force, and can completely adsorb the whole hole wall. With the growth of hole metallization treatment time, that is, the black hole time of flexible copper-clad board in graphene oxide solution increases, the carboxyl group in graphene oxide molecule and copper undergo complexation reaction to form metal intermetallic complex, and now the hole wall and graphene oxide layer directly form the molecular bond force with strong bonding force, and will not fall off in subsequent copper plating process, and the hole wall is smooth and flat after copper is deposited on the inner wall of through hole, and there is no defect, and the problem of plating leakage will not occur. In addition, compared with other hole metallization processes, the conductive layer thickness of graphene oxide hole metallization is thinner, and it is more suitable for high-frequency circuit board production.
[0019] The hole metallization method of the present invention does not contain formaldehyde carcinogens and chemical solutions that harm the ecological environment. The entire production process is harmless to humans, and graphene oxide wastewater can be reused to avoid waste and environmental pollution. At the same time, the process is simple, the efficiency is improved, human resource costs can be saved, and higher economic benefits can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 This is a metallographic microscope image of a section of the electroplated copper layer of the flexible copper-clad laminate provided in Example 1 of the present invention after the graphene oxide black hole treatment for 2 minutes.
[0022] Figure 2 This is a metallographic microscope image of a section of the electroplated copper layer of the flexible copper-clad laminate provided in Example 2 of the present invention after graphene oxide black hole treatment for 4 minutes.
[0023] Figure 3 This is a metallographic microscope image of a section of the electroplated copper layer of the flexible copper-clad laminate provided in Example 3 of the present invention after the graphene oxide black hole treatment for 6 minutes.
[0024] Figure 4 This is a metallographic microscope image of a section of the electroplated copper layer of the flexible copper-clad laminate provided in Example 4 of the present invention after the graphene oxide black hole treatment for 8 minutes.
[0025] Figure 5 This is a metallographic microscope image of a section of the electroplated copper layer of the flexible copper-clad laminate provided in Comparative Example 1 of the present invention after conventional carbon black black hole treatment for 4 minutes.
[0026] Figure 6 It is a metallographic microscope image of a section of the electroplated copper layer of the flexible copper-clad laminate provided in Comparative Example 2 of the present invention.
[0027] Figure 7 It is a metallographic microscope image of a section of the electroplated copper layer of the flexible copper-clad laminate provided in Comparative Example 3 of the present invention.
[0028] Figure 8 It is a metallographic microscope image of a section of the electroplated copper layer of the flexible copper-clad laminate provided in Comparative Example 4 of the present invention.
[0029] Fig. 9 It is a metallographic microscope image of a section of the electroplated copper layer of the flexible copper-clad laminate provided in Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] In the description of the present invention, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0032] The embodiment of the present invention provides a method for metallizing graphene oxide holes in a flexible copper-clad laminate, wherein the flexible copper-clad laminate with through holes is immersed in a graphene oxide aqueous solution and then subjected to chemical copper plating.
[0033] As a further improvement, the concentration of the graphene oxide aqueous solution is 18-24wt%, and the processing time is 2-10min. The graphene oxide is formed by a sufficient oxidation reaction of potassium permanganate and graphite powder in concentrated sulfuric acid. Further, the preparation of graphene oxide is to add graphite solid powder to concentrated sulfuric acid with a concentration of 98% and stir evenly, and then slowly add potassium permanganate in 5 times after the mixed liquid is cooled, and centrifuge to obtain graphene oxide flakes after the mixed liquid is cooled to room temperature. Among them, the ratio of concentrated sulfuric acid, graphite solid powder, and potassium permanganate is 180-220mL:1.5-2.5g:8-12g, preferably 200mL:2g:10g. The graphene oxide solution prepared by this method has good dispersibility, can be evenly dispersed in an aqueous solution, and does not agglomerate when placed for a long time. The microstructure of graphene oxide is flaky and is easily adsorbed on the surface of the copper hole wall, which is conducive to the smooth progress of hole metallization. At the same time, potassium permanganate is added in 5 times, with the addition method of adding a small amount at first, then gradually increasing, and finally reducing. This addition method makes the graphene oxide molecule have a carboxylic acid group on the edge of the carbon ring and a phenolic hydroxyl group and epoxy group on the carbon layer plane. It also contains a lot of carboxyl groups. The carboxyl group reacts with copper to produce an intermetallic complex. At this time, the pore wall and the graphene oxide layer directly form a strong molecular bond, and it will not fall off in the subsequent copper plating process.
[0034] As a further improvement, ultrasonic treatment is also performed during the immersion treatment to make the graphene oxide more evenly dispersed in the solution, so that the graphene oxide sheets are more evenly adsorbed on the pore walls. Preferably, the frequency range of the ultrasonic wave in the ultrasonic treatment is 20-60kHz, preferably 40kHz, which is most conducive to the dispersion of graphene oxide.
[0035] As a further improvement, before the immersion treatment, the through-holes of the flexible copper-clad laminate are also treated with a pore-sizing agent. Pore-sizing is also called degreasing, and its purpose is to remove oil stains or other impurities on the surface of the copper-clad laminate and make the through-holes of the flexible copper-clad laminate electronegative; the flexible copper-clad laminate that has been treated with pore-sizing is easy to adhere to the conductive layer, and the copper-clad laminate is immersed in a graphene oxide suspension with ultrasonic vibrations, and the hole metallization can be completed by keeping it for a certain period of time. The pore-sizing step is provided with an ultrasonic generator, so that the electronegativity of the hole wall is more uniform. Furthermore, the frequency range of the ultrasonic wave is 40-60kHz. Preferably, when the frequency of the ultrasonic wave is 45kHz, it is most conducive to the dispersion of graphene oxide.
[0036] The main component of the pore-shaping agent is an anionic surfactant, such as polyacrylamide. Since the hydrogen bonds of polyacrylamide combine with the oxygen-containing functional groups in graphene oxide to form van der Waals bonds, the adhesion of graphene oxide to the pore wall is further improved. The concentration range of the pore-shaping agent is 15-30wt%, and the pH range is 9-12. At this concentration and pH, hydrogen bonds are most easily formed in polyacrylamide surfactants. The temperature range is 30-40°C, which is beneficial to the combination of hydrogen bonds and oxygen-containing functional groups.
[0037] As a further improvement, after the immersion treatment, the through holes of the flexible copper clad laminate are also micro-etched with a micro-etching solution. The micro-etching solution is a mixed solution of 60-90 g / L sulfuric acid and 30-50 g / L sodium persulfate. The micro-etching temperature of the micro-etching solution is 30-35°C, and the micro-etching time is 40-90 seconds. This micro-etching solution has good compatibility with graphene oxide and will not damage the GO adhesion layer; this temperature and time are based on considerations of the protectiveness of the GO adhesion layer.
[0038] As a further improvement, the through hole is formed by drilling a hole on the surface of the flexible copper-clad laminate using an ultraviolet laser drilling machine. The ultraviolet laser drilling machine is a 355nm picosecond ultraviolet laser drilling machine, the drilling power is 4.5W, the scanning speed is 50mm / s, and the number of repeated drillings is 4 times. Under this drilling condition, the hole wall has a special texture, which is conducive to the attachment of graphene oxide.
[0039] As a further improvement, the temperature of the chemical copper plating is 30-42°C, and the copper plating time is 5-15 minutes. The chemical copper plating process can control the copper plating thickness more accurately, and the hole wall is rarely missed. The copper plating thickness is 15-20μm, preferably 18μm.
[0040] The embodiment of the present invention also provides a flexible copper-clad laminate prepared by the above method. The flexible copper-clad laminate can be a double-sided copper-clad laminate or a multi-layer copper-clad laminate. After copper is deposited on the inner wall of the through hole, the hole wall is smooth and flat, without defects, and there is no problem of plating leakage; at the same time, compared with other hole metallization processes, the thickness of the conductive layer of the graphene oxide hole metallization is thinner, which is very suitable for the production of flexible circuit boards, especially for the production of high-frequency circuit boards.
[0041] Example 1
[0042] The specific process steps of metallizing the graphene oxide holes of the flexible copper-clad laminate of the present invention are as follows:
[0043] The first step is to use ultraviolet laser drilling to drill several through holes on the flexible copper clad board; a 355nm picosecond ultraviolet laser drilling machine is used, the power of the ultraviolet laser drilling machine is 4.5W, the scanning speed is 50mm / s, and the number of repeated drilling times is 4 times.
[0044] In the second step, the flexible copper-clad laminate with holes is washed with circulating water, and then the holes of the flexible copper-clad laminate are treated with a hole-forming agent, polyacrylamide. The concentration range of the hole-forming agent is 20wt%, the pH range is 10, and the temperature is set to 35°C. Ultrasonic treatment is used during the hole-forming process, and the frequency is 45kHz.
[0045] The third step is to add 2 g of graphite solid powder to 200 ml of 98% sulfuric acid and stir evenly. After the mixed liquid is cooled, 10 g of potassium permanganate is slowly added in 5 times (1.5 g for the first time, 2 g for the second time, 3 g for the third time, 2 g for the fourth time, and 1.5 g for the fifth time). After the mixed liquid is cooled to room temperature, it is centrifuged to obtain graphene oxide flakes, and pure water is added to form a 20 wt% graphene oxide solution.
[0046] In the fourth step, the flexible copper clad board is immersed in the graphene oxide suspension for 2 minutes to perform black hole treatment. Ultrasonic treatment is used during the immersion process at a frequency of 40 kHz.
[0047] In the fifth step, the flexible copper-clad laminate after the black hole is immersed and sprayed in a micro-etching solution of 80g / L sulfuric acid and 40g / L sodium persulfate mixed solution to achieve the purpose of micro-etching. The temperature of the micro-etching solution is 32°C, and the micro-etching time of the copper-clad laminate is 60s.
[0048] The sixth step is to perform chemical copper plating on the washed flexible copper-clad laminate. The temperature of the chemical copper plating is 36° C. and the copper plating time is 10 minutes.
[0049] Graphene oxide is used to treat the hole wall of the flexible copper clad board for two minutes. The copper layer on the hole wall is electroplated. Figure 1 As shown, the bottom of the hole is round and complete without black spots, the copper thickness of the hole is uniform, there are a few defects at the hole mouth, and there are no voids or delamination.
[0050] Example 2
[0051] The difference from Example 1 is that the black hole treatment time is 4 minutes, and the other operations are the same as Example 1.
[0052] Graphene oxide was used to treat the hole wall of the flexible copper-clad board for 4 minutes, and the copper layer on the hole wall was electroplated. Figure 2 As shown, the hole bottom is completely round without black spots, the hole copper thickness is uniform, there is no void or stratification, and it is the group with the best black hole effect.
[0053] Example 3
[0054] The difference from Example 1 is that the black hole treatment time is 6 minutes, and other operations are the same as Example 1.
[0055] Graphene oxide was used to treat the hole wall of the flexible copper clad board for 6 minutes, and the copper layer on the hole wall was electroplated. Figure 3As shown, the bottom of the hole is round and complete, with a small amount of black spots, the copper thickness of the hole is uniform, there is no void or delamination, and there are some defects at the hole mouth.
[0056] Example 4
[0057] The difference from Example 1 is that the black hole treatment time is 8 minutes, and other operations are the same as Example 1.
[0058] Graphene oxide was used to treat the hole wall of the flexible copper clad board for 8 minutes, and the copper layer on the hole wall was electroplated. Figure 4 As shown, the bottom of the hole is round and complete with black spots, the copper thickness of the hole is uniform, there are no voids or stratification, and there are some defects at the hole mouth.
[0059] Comparative Example 1
[0060] The conventional carbon black suspension was used for the through-hole metallization of the flexible circuit board, and the other operations were the same as those in Example 1.
[0061] The carbon black suspension is prepared by adding carbon black powder and dispersant sodium tripolyphosphate into DI water, wherein the mass fraction of the carbon black powder is 3% and the mass fraction of the dispersant is 4%, and then fully dispersing the carbon black powder by ultrasonic vibration to prepare the carbon black suspension.
[0062] Carbon black suspension was used to treat the hole wall of the flexible copper clad laminate for four minutes. The copper layer on the hole wall was electroplated. Figure 5 As shown, the hole wall plating is more than 6um, but there is residual copper accumulated in the hole to the hole mouth, and the hole bottom plating and base copper are delaminated.
[0063] Comparative Example 2
[0064] The power of the ultraviolet laser drilling machine is 10 W, the scanning speed is 60 mm / s, the number of repeated drilling is 1, and the other operations are the same as in Example 1.
[0065] The hole wall electroplated copper layer is as follows Figure 6 As shown, since the laser drilling parameters are not optimal parameters, there are more residues in the drilled holes. During copper plating, copper is deposited on the residues, resulting in copper nodules in the holes.
[0066] Comparative Example 3
[0067] The pore-regulating agent is ethylene oxide and propylene oxide copolymer, and other operations are the same as those in Example 1.
[0068] The hole wall electroplated copper layer is as follows Figure 7 As shown, due to the poor adsorption of ethylene oxide propylene oxide copolymer with GO, it is unable to provide hydrogen bonds with GO, GO cannot be uniformly attached to the hole wall, GO is deposited in the hole, resulting in thick copper deposition in the hole of the electroplated copper layer.
[0069] Comparative Example 4
[0070] In the preparation of graphene oxide, potassium permanganate is added once, and other operations are the same as in Example 1.
[0071] The hole wall electroplated copper layer is as follows Figure 8 As shown in the figure, due to the one-time addition of potassium permanganate, GO cannot form enough carboxyl groups, and the complexation reaction between carboxyl groups and copper is reduced, resulting in GO deposition at the bottom of the hole and excessively thick copper plating at the bottom.
[0072] Comparative Example 5
[0073] The micro-etching solution is 40 g / L sulfuric acid and 80 g / L sodium persulfate, and the rest is the same as in Example 1.
[0074] The hole wall electroplated copper layer is as follows Fig. 9 As shown, the micro-etching solution has poor compatibility with GO at this concentration, and part of GO will be carried out of the hole wall by the micro-etching solution, resulting in poor electrical conductivity of the hole wall, poor copper plating effect, and too thin copper plating on the hole wall.
[0075] It can be seen from Examples 1-4 and Comparative Examples 1-5 that the method for metallizing the graphene oxide holes in the flexible copper clad laminate of the embodiment of the present invention is mainly to perform hole metallization treatment on the flexible copper clad laminate using a graphene oxide solution. At the same time, by adjusting the punching process, the selection and use process of the pore-forming agent, the preparation and use process of graphene oxide, the micro-etching process and the copper plating process, each process interacts with the graphene oxide to play a synergistic effect, promotes the adhesion of graphene oxide to the hole wall and the formation of the copper plating layer, thereby forming a uniform, fine and firmly bonded conductive layer, the reliability of the electroplated copper layer is higher, and the hole wall is smooth and flat after copper is deposited on the inner wall of the through hole, without defects, and there will be no problem of missing plating.
[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for metallizing graphene oxide holes in a flexible copper-clad laminate, characterized in that: A flexible copper-clad laminate with through holes is immersed in a graphene oxide aqueous solution and then subjected to chemical copper plating; the concentration of the graphene oxide aqueous solution is 18-24wt%, and the treatment time is 2-10min; the graphene oxide is prepared by adding graphite solid powder to concentrated sulfuric acid with a concentration of 98% and stirring evenly, and after the mixed liquid is cooled, potassium permanganate is slowly added in 5 times, and the adding method is that the amount is first small, then gradually increased, and finally reduced, and after the mixed liquid is cooled to room temperature, centrifugal precipitation is performed to obtain graphene oxide flakes; wherein, the ratio of concentrated sulfuric acid, graphite solid powder, and potassium permanganate is 180-220mL:1.5-2.5g:8-12g.
2. The method for metallizing graphene oxide holes in a flexible copper-clad laminate according to claim 1, characterized in that: Ultrasonic treatment is also performed during the soaking process.
3. The method for metallizing graphene oxide holes in a flexible copper-clad laminate according to claim 2, characterized in that: The frequency range of the ultrasonic wave in the ultrasonic treatment is 20-60 kHz.
4. The method for metallizing graphene oxide holes in a flexible copper clad laminate according to claim 1, characterized in that: Before the immersion treatment, the through holes of the flexible copper clad laminate are also treated with a hole-leveling agent.
5. The method for metallizing graphene oxide holes in a flexible copper clad laminate according to claim 1, characterized in that: After the immersion treatment, the through holes of the flexible copper clad laminate are also micro-etched using a micro-etching solution.
6. The method for metallizing graphene oxide holes in a flexible copper-clad laminate according to claim 1, characterized in that: The through holes are formed by drilling holes on the surface of the flexible copper-clad laminate using an ultraviolet laser drilling machine.
7. The method for metallizing graphene oxide holes in a flexible copper-clad laminate according to claim 6, characterized in that: The power of the ultraviolet laser drilling machine is 4.5W, the scanning speed is 50mm / s, and the number of repeated drilling times is 4 times.
8. A flexible copper clad laminate prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Hole metallization method for flexible printed circuit board
CN104582324A
Graphene metallization solution and preparation method and application thereof
CN108834309A
Cited By
Method for activating thick copper PCB (Printed Circuit Board) hole before metallization based on dispersant-free graphene copper-plating pre-activating solution
CN116017885A
A method for pre-metallization activation of thick copper PCB board holes using a dispersant-free graphene pre-copper plating activation solution.
CN116017885B